Analysis of the Process of Implementing Analog Land Certificates to Electronics at the National Land Office of Palopo City - Ecce Jumsa; Salmi; Hisma Kahman (CV Edujavare Publishing, 2026)
This study aims to analyze the implementation of the conversion of analog land certificates into electronic certificates as an effort to strengthen legal protection and ensure certainty of land ownership rights. Using a normative-empirical research approach, the study examines both the legal framework governing electronic land registration and its practical implementation. The analysis is based on primary legal materials and empirical data, which are interpreted qualitatively and presented descriptively. The findings indicate that the issuance of electronic certificates follows a structured process involving comprehensive verification and validation of physical, juridical, and ownership data before the certificate is issued. The implementation is primarily guided by the Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) Number 3 of 2023. The study also confirms that analog and electronic certificates possess equal legal validity as evidence of land ownership. However, several challenges remain, particularly public concerns regarding data security and the extensive verification process required to validate land records. As experienced by the National Land Agency of Palopo City, these challenges have delayed the issuance of some electronic certificates, requiring unprocessed applications to be carried forward to the following year.